Causes and Consequences of Gray Matter Heterotopia - Watrin, Françoise (CNS Neurosci Ther, 2014)
The objective of this article is to review the pathophysiological bases of gray matter heterotopia and to appreciate their involvement in brain cortical development and functional consequences, namely epilepsy. The development of the cerebral cortex results from complex sequential processes including cell proliferation, cell migration, cortical organization, and formation of neuronal networks. Disruption of these steps yields different types of cortical malformations including gray matter heterotopia, characterized by the ectopic position of neurons along the ventricular walls or in the deep white matter. Cortical malformations are major causes of epilepsy, being responsible for up to 40% of drug‐resistant epilepsy, and the cognitive level of affected patients varies from normal to severely impaired. This review reports data from human patients and animal models highlighting the genetic causes for these disorders affecting not only neuronal migration but also the proliferation of cortical progenitors. Therefore, gray matter heterotopias should not be considered as solely due to an abnormal neuronal migration and classifying them as such may be too restrictive. The review will also summarize literature data indicating that besides ectopic neurons, neighbor cortical areas also play a consistent role in epileptogenesis, supporting the notion that plastic changes secondary to the initial malformation are instrumental in the pathophysiology of epilepsy in affected patients.